Verso l' Ut Omnes - Towards Ut Omnes - Chenaux, Philippe; Žak, Lubomir (Brepols, 2021)
The studies collected in this volume highlight the rising of an ecumenical consciousness within the Catholic Church in the early twentieth century. The Catholic paths, suggested in view of the hoped-for Christian unity before the Second Vatican Council, were different but complementary: the path of prayer and liturgy, that of theological refl ection, that of fraternal witness and that of martyrdom. The text offers valuable contributions on all these paths, written by specialists in the history of ecumenism.